Molecular characterization of endometrial cancer and therapeutic implications. Issue 1 (February 2017) - Uppendahl, Locke; Mullany, Sally A.; Winterhoff, Boris
Abstract : Purpose of review: This article reviews the emerging comprehensive genomic classification of endometrial carcinoma and discusses the therapeutic implications of these subgroups. Recent findings: Comprehensive, multiplatform evaluation of endometrial cancers by the Cancer Genome Atlas stratified the molecular aberrations into four distinct subtypes: POLE mutations, microsatellite instability, copy-number low/microsatellite stable, and copy-number high/'serous-like.' POLE -mutant tumors have a favorable prognosis and may often be overtreated. Microsatellite instability hypermutated tumors commonly have alterations in the phosphatidylinositide 3-kinases/AKT/mechanistic target of rapamycin pathway and limiting targeted therapy to this group may lead to greater response rates. Copy-number low/microsatellite stable tumors represent the majority of grade 1 and grade 2 endometrioid cancers and have an intermediate prognosis, few TP53 mutations, but frequent mutations in genes involved with Wingless-related integration site signaling. Approximately 25% of high-grade endometrioid tumors have mutational profiles that classify as copy-number high/'serous-like' and might benefit from treatment approaches similar to those for serous tumors. Summary: Molecular characterization of endometrial cancer classifies tumors into prognostically significant subtypes with a broad range of therapeutic implications.